Alternatives to bureaucracy based on worker participation and horizontal management: Why do they work? - Estrago, Alfonso Manuel (2025)
Administration is an academic field that is showing signs of maturity, with a theoretical and practical mainstream that has been consolidated around Weberian bureaucracy, a management paradigm with numerous examples suggesting that it may be reaching its limits in terms of the new advances it can offer the discipline. On the other hand, the shift to a paradigm that transcends it (while retaining all its virtues) requires not only successful empirical counter-examples, but also a consistent alternative theoretical corpus that gives academics and especially practitioners the confidence to adopt it. In this sense, through “integrative” literature review-based research, the article intends to outline a scholarly narrative that provides concrete theoretical underpinnings to explain, in a systematic and concise manner, why management styles that depart significantly from bureaucratic orthodoxy are stable (i.e., do not diverge towards “chaos and anarchy”), while also proving effective and efficient. As a result of the analysis carried out, an intertwined combination of contributions about alternatives to the classical bureaucratic arrangement is obtained, sourced from studies of different time periods. Thence, based on four conceptual axes (self-actualization, objectives, capabilities and monitoring), the elaboration of a theoretically integrated explanation for the sustainable viability of participatory and horizontal management is achieved. This article’s contribution points towards the future possibility of consolidating novel approaches that virtuously supplant the current bureaucratic mainstream.